2013
DOI: 10.1371/journal.pone.0069066
|View full text |Cite
|
Sign up to set email alerts
|

Localization and Expression of Hsp27 and αB-Crystallin in Rat Primary Myocardial Cells during Heat Stress In Vitro

Abstract: Neonatal rat primary myocardial cells were subjected to heat stress in vitro, as a model for investigating the distribution and expression of Hsp27 and αB-crystallin. After exposure to heat stress at 42°C for different durations, the activities of enzymes expressed during cell damage increased in the supernatant of the heat-stressed myocardial cells from 10 min, and the pathological lesions were characterized by karyopyknosis and acute degeneration. Thus, cell damage was induced at the onset of heat stress. Im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 47 publications
2
25
0
Order By: Relevance
“…These enzymes are generally designated as cardiomyocyte damage-related enzymes and further regarded as important indicators for judging acute myocardial injury (Amani et al 2013;Chen et al 2013;Chon et al 2013;Wu et al 2013), especially CK-MB (Zeren et al 2013). In addition to these enzymes, cytopathological changes like swollen in size, uneven staining in the cytoplasm and vacuolar degeneration were clearly identified in a lot of researches (Chen et al 2015;Tang et al 2013). According to these myocardial cell damage markers, it is clearly to find that overexpressed HspB1 by ASA was accompanied with relatively slight heat stress injury in myocardial cells, while severe cell damage appeared when ASA was not involved and the HspB1 level In the ASA-HS group and the ASA group, HspB1 concentration almost kept two orders of magnitude higher than the HS group in which the only HspB1 inducer was high temperature…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These enzymes are generally designated as cardiomyocyte damage-related enzymes and further regarded as important indicators for judging acute myocardial injury (Amani et al 2013;Chen et al 2013;Chon et al 2013;Wu et al 2013), especially CK-MB (Zeren et al 2013). In addition to these enzymes, cytopathological changes like swollen in size, uneven staining in the cytoplasm and vacuolar degeneration were clearly identified in a lot of researches (Chen et al 2015;Tang et al 2013). According to these myocardial cell damage markers, it is clearly to find that overexpressed HspB1 by ASA was accompanied with relatively slight heat stress injury in myocardial cells, while severe cell damage appeared when ASA was not involved and the HspB1 level In the ASA-HS group and the ASA group, HspB1 concentration almost kept two orders of magnitude higher than the HS group in which the only HspB1 inducer was high temperature…”
Section: Discussionmentioning
confidence: 99%
“…Such injuries will change the permeability of the myocardial cell membrane and cause the release of a series of enzymes such as creatine kinase-MB (CK-MB) and lactate dehydrogenase (LDH) (Saravanan et al 2013). Increases of these myocardial cell damage-related enzymes have been clearly detected after heat stress (Tang et al 2013;Yan et al 2009). Moreover, heat stress exposure leads to obvious pathological changes.…”
Section: Introductionmentioning
confidence: 99%
“…The damages caused by heat stress to breeding industries have been explained in our previous works, especially the considerable economic loss on poultry breeding (Wu et al 2015(Wu et al , 2016. Previous research also has revealed that acute HS leads to cardiac dysfunction and other forms of myocardial cell damage (Tang et al 2013), and these effects are responsible for sudden infant death in animals and even in humans after HS exposure (Gathiram et al 1987(Gathiram et al , 1988Rai and Ambwany 1980).…”
Section: Introductionmentioning
confidence: 92%
“…HS exposure increases the permeability of myocardial cells, causing a series of enzymes such as isoenzyme creatine kinase-MB (CK-MB) and lactate dehydrogenase (LDH) to be released from the myocardial cells (Ma et al 2013;Xue et al 2015). These enzymes are categorized as myocardial cell damage-related enzymes and are widely used as markers of myocardial cell injury (Saravanan et al 2013;Tang et al 2013;Wu et al 2015). In addition to these enzymes, histopathological or cytopathological damages are also commonly observed in myocardial cells after HS; for example, the cells may be swollen in size, show uneven matrix staining in the cytoplasm, appear shrunken and dull-stained in the nucleus, or exhibit acute degeneration (Tang et al 2013;Wu et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The chief impact of HSF1 activation is the elevated production of HSPs whose major representative is HSP70. Small heat shock proteins induced by fever, such as HSP27, also contribute to cytoprotection [82,83].…”
Section: Anti-inflammatory Role Of Intracellular Hsp70mentioning
confidence: 99%